Factors Predicting Adherence to an Integrative Model of Care Intervention in Hispanic/Latino Patients with Type II Diabetes (P04-118-19). (13th June 2019) - Pompano, Laura; Gallo, Linda; Castañeda, Sheila; Garcia, Melawhy; Muñoz, Fatima; Martinez-Mendoza, Paulina; Talavera, Gregory
Abstract: Objectives: This study aimed to identify factors relating to adherence to an integrative model of care intervention for Hispanic/Latino patients with type 2 diabetes (T2D). Methods: Baseline characteristics and 12-month intervention data from 225 Hispanic/Latino patients with T2D who were randomized to the intervention arm of the Latinos Understanding the Need for Adherence in Diabetes (LUNA-D) trial were analyzed. Linear regressions were conducted to determine which factors (sex, age, BMI, place of birth, family diabetes history, annual household income, employment, education, current smoking, marital status, controlled or uncontrolled glycated hemoglobin [HbA1c,  ≤ 7% or > 7%, respectively], depression, anxiety, or diabetes distress) predicted adherence to three intervention components: group health education classes (GHEC), behavior health consultations (BHC), and medical examinations (ME). Logistic regression was conducted to identify factors that predicted poor (≤50%) or adequate ( > 50%) adherence to the total intervention. Results: Results of linear regressions are means ± standard error. Controlled HbA1c status predicted poorer GHEC (β = −1.9 ± 4.7, P  < 0.001) and BHC adherence (β = −1.7 ± 0.3, P  < 0.001). Higher diabetes distress also predicted poorer BHC attendance (β = −0.99 ± 0.30). Adherence to ME visits was worse for participants with controlled HbA1c (β = −1.77 ± 0.29, P  < 0.001) and higher diabetes distress (β = −1.00 ± 0.30) but was better for those with increased anxiety (β = 0.10 ± 0.05, P  = 0.043). No other factors predicted adherence. Factors significantly predicting > 50% adherence to all intervention components were: poorly controlled HbA1c (OR = 6.2, 95% CI: 3.0, 12.6, P  < 0.001), higher anxiety (OR = 1.2, 95% CI: 1.0, 1.3, P  = 0.024), higher diabetes distress (OR = 0.45, 95% CI: 0.22, 0.92, P  = 0.29), and higher age (OR = 1.1, 95% CI: 1.0, 1.1, P  = 0.014). Conclusions: Having uncontrolled T2D predicts better adherence to GHEC, BHC, and ME in Hispanics/Latinos with T2D. However, different factors appear to influence specific adherence to medical examinations and behavioral health consultations. T2D interventionists should target specific factors to improve adherence to multi-component interventions for Hispanic/Latino patients. Funding Sources: NIH/NINR.